2001
DOI: 10.1038/35087518
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ubiquitous strong electron–phonon coupling in high-temperature superconductors

Abstract: Coupling between electrons and phonons (lattice vibrations) drives the formation of the electron pairs responsible for conventional superconductivity 1 . The lack of direct evidence for electron-phonon coupling in the electron dynamics of the high transition temperature superconductors has driven an intensive search for an alternative mechanism. A coupling of an electron with a phonon would result in an abrupt change of its velocity and scattering rate near the phonon energy. Here we use angle resolved photoem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

115
1,401
7
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,407 publications
(1,528 citation statements)
references
References 26 publications
115
1,401
7
5
Order By: Relevance
“…Figure 9 displays frequency dependencies of the ratios E loc bl /E, E loc int /E and E loc ocp /E in the SCS obtained using Eqs. (4)- (12). The phonons have not been taken into account and S bl = 0.…”
Section: Composite Vibrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 9 displays frequency dependencies of the ratios E loc bl /E, E loc int /E and E loc ocp /E in the SCS obtained using Eqs. (4)- (12). The phonons have not been taken into account and S bl = 0.…”
Section: Composite Vibrationsmentioning
confidence: 99%
“…It is important to establish what particular type of electron-phonon interaction is responsible for these effects (so called phonon anomalies), and whether the anomalous phonons are "active players" in the mechanism of the high-T c superconductivity [11,12,13] or whether they simply respond to changes of the electronic ground state that have an independent cause. Here we focus on the anomalies of c-axis polarized infrared-active phonons.…”
Section: Introductionmentioning
confidence: 99%
“…Recent photoemission experiments in the high-Tc cuprates [1,2,3,4], which are generally described in terms of purely electronic models due to the proximity to a Mott insulating phase, have revealed the existence of an important electron-lattice coupling. This has given rise to intense theoretical work focusing on the excitation spectra in the presence of electron-boson interactions, both in models with [5,6,7] and without [8,9,10,11,12,13] electronic correlations.…”
mentioning
confidence: 99%
“…[79] In examining the mass enhancement some groups have focused more closely on the associated "kink" in the dispersion and suggested that its presence at a similar energy in studies of all of the different cuprates is an indication of coupling to a phonon mode. [75] Indeed neutron studies do indicate the presence of phonon modes at similar energies. [80] The authors of these studies have also suggested that an "unconventional isotope effect" is an indication of the role of phonons in that the substitution of O 18 for O 16 results in a change in the velocity of the higher energy electrons as opposed to the lower energy electrons in the vicinity of the Fermi level.…”
Section: Studies Of the High T C Superconductorsmentioning
confidence: 99%
“…This observation has potentially important implications for the mechanism driving high T C superconductivity and an obvious question is whether or not it points to a BCS like mechanism whereby the electrons or renormalization and associated "kink" have become central issues in subsequent ARPES work with considerable controversy regarding their source. [73,74,75,76,77] Are they related to the presence of spin excitations or do they reflect an interaction with phonons or indeed any other collective mode? In the case of the cuprates, this is not an easy issue to resolve as the various energy scales are nearly identical.…”
Section: Studies Of the High T C Superconductorsmentioning
confidence: 99%